Aryl hydrocarbon receptor deficiency leads to sex- and age-dependent colonic dysmotility in mice - Alicia Valls; David Verdú; Sol Guerra-Ojeda; Teresa San-Miguel; Andrea Suarez; Javier Pereda; Verónica Gómez-Jiménez; José Viña; Maria D Mauricio; Eva Serna (Journal of Physiology and Biochemistry, 2026)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor involved in xenobiotic sensing and multiple physiological functions, including intestinal homeostasis. Aging is associated with reduced colonic motility and constipation, but the contribution of AhR to intestinal motor function across sex and age remains incompletely defined. We performed a phenotypic characterization of AhR-deficient (AhR −/− ) and wild-type (WT) C57BL/6J mice in both sexes at two ages (young: 4–6 months; adult: 12–13 months). Lifespan, body weight, food and water intake were monitored longitudinally. Body composition (DXA), hematological parameters, fecal output features (number, length, moisture and stool color analysis), ex vivo colonic function in organ bath (spontaneous peristalsis with or without L-NAME and responses to acetylcholine and norepinephrine), histological muscle thickness, and molecular markers (PGP9.5 and NOS1 protein; Nos1 , Nos2 , Aqp1/3/4/8 , Il6 , Il10 gene expression) were assessed. AhR −/− mice exhibited reduced survival and attenuated body weight gain, particularly in females, without differences in food consumption but with increased water intake. Fecal length and moisture were unchanged; however, AhR −/− females displayed fewer stools at both ages. Ex vivo, spontaneous peristaltic amplitude was selectively reduced in AhR −/− females at both ages, whereas males were unaffected. L-NAME increased spontaneous peristalsis in WT males but not in AhR −/− males, suggesting impaired nitrergic modulation in the absence of AhR. Acetylcholine-induced contraction was reduced in young AhR −/− females but not in adults. Histology revealed reduced colonic muscle thickness in young AhR −/− females only, accompanied by decreased PGP9.5 protein expression. Gene expression showed sex- and age-dependent changes in Nos1 / Nos2 , aquaporins, and inflammatory markers. AhR deficiency leads to a sex-dependent colonic motor phenotype predominantly affecting females, integrating functional impairment with early neuromuscular remodeling and altered neural markers. These findings support AhR as a regulator of intestinal motor function with potential relevance to age-related dysmotility.

Traffic-related air pollution in utero modifies cytokine responses to stimuli of umbilical cord blood cells: a cohort study - Azahara M. García-Serna; Elena Martín-Orozco; Pedro Jiménez-Guerrero; Trinidad Hernández-Caselles; Esther Cantero-Cano; María del Carmen Elena; Jesús Soler-Sánchez; Luis García-Marcos; Eva Morales (Environmental Research, 2026)

Urinary concentrations of non-essential and essential elements during weaning in infants from the NELA cohort in Spain - Leyre Notario-Barandiaran; Eva Morales; Jesús Vioque; Carmen Martinez-Gracia; Marina Santaella-Pascual; Clara Suarez-Martinez; Luis Garcia-Marcos; Margaret R. Karagas; Antonio J. Signes-Pastor; M.E. Candel-Torralba; L. Garcia-Marcos (Pi); M.J. Gimenez-Banon; et al. (Environmental Research, 2024)